Multi-factor controls on initial gas production pressure of coalbed methane wells in Changzhi-Anze block, Central-Southern of Qinshui Basin, China - Yang Zhao; Xiaodong Zhang; Shuo Zhang; Jiaosheng Yang; Xianzhong Li; Shuai Heng (Adsorption Science & Technology)
Adsorption and desorption of coalbed methane are generally at a dynamic equilibrium state under the undisturbed coal reservoir. However, as the reservoir pressure drops to a certain value during the extraction of coalbed methane, the equilibrium state is destroyed and thus more coalbed methane desorbs and escapes from coal to wellbore. Here the corresponding bottom-hole fluid pressure is called initial gas production pressure (IGPP) in the development practice of coalbed methane wells. This paper, which has taken Changzhi-Anze block in the central-southern part of Qinshui basin as the study object, addresses the distribution characteristic and control factors of IGPP of coalbed methane wells and then explores the key factors affecting IGPP using grey correlation analysis theory. The results indicate that IGPP varies from 1.09 MPa to 6.57 MPa, showing a distribution law with high in the middle and low in the west and east of the study area, which presents a similar distribution characteristic with burial depth, thickness, coal rank, gas content, original reservoir pressure, and in-situ stress. Further, through grey correlation analysis, it concludes that the correlation degrees of control factors affecting IGPP of coalbed methane wells in the descending order are decline rate of working fluid level, water yield before gas production, reservoir pressure, coal thickness, coal rank, minimum horizontal principal stress, burial depth, and gas content. Among these factors, engineering factors, including decline rate of working fluid level and water yield before gas production, present a key controlling effect, because they can determine the smooth migration pathway directly during initial water production. And another key factor, original reservoir pressure also builds strong and positive correlation with IGPP under the interaction of other geology and reservoir factors, revealing the capability of gas desorption and the transmission of pressure drops.